Análisis de datos en el Ministerio De Hacienda y Crédito Público - Santa Ibarra, Santiago (Universidad Antonio Nariño, 2023)
At the end of the undergraduate process as a student, you have to take a decision about which path to take as a degree project. Based on this the student chose the internship modality, where the Antonio Nariño University with its agreement 002 in annex 3 indicates the route to follow for the elaboration of the report of internship. When taking this option, go to the General Directorate of Economic Regulation of Social Security and find myself with the lack of pertinent application of the various data analysis tools that exist, it is decided to provide the support that is requested by this address through these tools. With the support of the boss directly from the management, the results and methods that will be exposed throughout the of the internship report.